A method of reproducing complex, multi-object anatomical structures. Issue 1 (16th January 2017) - Kudasik, Tomasz; Miechowicz, Slawomir
Abstract : Purpose: This paper aims to present a method of reproducing multi-object structures from materials of diverse physical properties with the use of models fabricated by means of rapid prototyping (RP) techniques. Design/methodology/approach: A process of modelling complex anatomical structures of soft tissues and bones using mandible models as examples was described. The study is based on data acquired through standard computed tomography. Physical models of examined objects were fabricated with RP technology from a 3D-CAD virtual model. Findings: In the analysis of complex medical issues, beside numerical methods, one can simultaneously make use of experimental tests to verify obtained results. In the case of experimental tests, it is necessary to fabricate physical models with appropriate material properties. RP techniques used in the method ensure accurate reproduction of the external shape of the fabricated model, whereas consecutive stages allow us to construct moulds and create internal structures within a finished model by wax cast models. Practical implications: The application of a physical RP model makes the identification of medical problem more efficient and the reconstruction of pathological alterations for experimental tests clearer. It prevents the simplification of assumptions to experimental analysis. The approach may reduce costs of fabricating models for experimental studies and offers the possibility of using materials of desired properties. Originality/value: The approach developed by the authors and presented in this paper was submitted for patent protection as "A Method of Reconstructing Medical Models with Internal Structure and the Use of Materials of Diverse properties" – patent application no. P.398644.